Cyclodextrin‐Derived ROS‐Generating Nanomedicine with pH‐Modulated Degradability to Enhance Tumor Ferroptosis Therapy and Chemotherapy. Issue 20 (22nd April 2022) - Xu, Meng; Zha, Haidong; Han, Run; Cheng, Yaxin; Chen, Jiamao; Yue, Ludan; Wang, Ruibing; Zheng, Ying
Abstract: Nowadays, destruction of redox homeostasis to induce cancer cell death is an emerging anti‐cancer strategy. Here, the authors utilized pH‐sensitive acetalated β‐cyclodextrin (Ac‐β‐CD) to efficiently deliver dihydroartemisinin (DHA) for tumor ferroptosis therapy and chemodynamic therapy in a synergistic manner. The Ac‐β‐CD‐DHA based nanoparticles are coated by an iron‐containing polyphenol network. In response to the tumor microenvironment, Fe 2+ /Fe 3+ can consume glutathione (GSH) and trigger the Fenton reaction in the presence of hydrogen peroxide (H2 O2 ), leading to the generation of lethal reactive oxygen species (ROS). Meanwhile, the OO bridge bonds of DHA are also disintegrated to enable ferroptosis of cancer cells. Their results demonstrate that these nanoparticles acted as a ROS generator to break the redox balance of cancer cells, showing an effective anticancer efficacy, which is different from traditional approaches. Abstract : A reactive oxygen species (ROS)‐generating nanomedicine based on acetalated β‐cyclodextrin loaded with dihydroartemisinin and coated with an iron‐containing polyphenol network can move the active redox reaction in cancer cells to the side of the excessive ROS production, so as to realize a redox dyshomeostasis strategy against malignant tumors.